2019
DOI: 10.1242/jcs.228452
|View full text |Cite
|
Sign up to set email alerts
|

Chemically induced neurite-like outgrowth reveals a multicellular network function in patient-derived glioblastoma cells

Abstract: Tumor stem cells and malignant multicellular networks have been separately implicated in the therapeutic resistance of glioblastoma multiforme (GBM), the most aggressive type of brain cancer in adults. Here, we show that small-molecule inhibition of RHO-associated serine/threonine kinase proteins (ROCKi) significantly promoted the outgrowth of neurite-like cell projections in cultures of heterogeneous patient-derived GBM stem-like cells. These projections formed de novo-induced cellular network (iNet) 'webs', … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
3
4
0
Order By: Relevance
“…As expected, Calcium exchange increased upon TGF-β1 stimulation and was inhibited by LY2157299. Network formation and increase in Calcium exchange in GBM cells in vitro was also observed by da Silva et al using ROCK inhibition [9].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…As expected, Calcium exchange increased upon TGF-β1 stimulation and was inhibited by LY2157299. Network formation and increase in Calcium exchange in GBM cells in vitro was also observed by da Silva et al using ROCK inhibition [9].…”
Section: Discussionsupporting
confidence: 56%
“…Calcium signal spread across cells was carried out as previously described [9]. Fluo-3-AM (Thermo Fisher Scientific, F23915) was added to the cells and incubated for 30 min in the dark at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Network formation and increase in calcium exchange in GBM cells in vitro was also observed by da Silva et al using ROCK inhibition. 19 The majority of our cell lines responded to TGF-β1 with increase in MT formation. Interestingly, we identified one cell line (GG6), which did not respond and also showed very limited invasive capacity upon TGF-β stimulation using ex vivo brain organoid co-cultures and in vivo xenografts.…”
Section: Discussionmentioning
confidence: 87%
“…Calcium signal spread across cells was carried out as previously described. 19 Fluo-3-AM intensity was determined using the ImageJ z-axis profile function. Mean fluorescence intensity was determined from 20 time lapses per condition.…”
Section: In Vitro Calcium Imagingmentioning
confidence: 99%
“…In some cases, ROCKi significantly decreased invasion and provided significant survival benefits in animal models of high-grade glioma [36,37]. Other times, ROCKi significantly increased invasion [38], stabilized pro-invasive tumor microtube networks, and decreased sensitivity to standard of care radiation and chemotherapy [39]. We previously demonstrated that both global activation and inhibition of mDia are effective anti-invasive and anti-tumor microtube strategies in GBM, with activation representing the superior approach [12,40].…”
Section: Introductionmentioning
confidence: 99%